Stridulation behaving in Heilipus odoratus Vanin & Gaiger (Coleoptera, Curculionidae, Molytinae) - Nunes, Adilson Benchaya (2020)
Heilipus odoratus Vanin & Gaiger, 2005 (Coleoptera, Curculionidae, Molytinae) is considered the main plague of rosewood fruit. Being recently described, the biological aspects of this species are not very well known. This study aimed at contributing for the knowledge of this species' behavior and providing a method for sexing adults based on stridulation. Individuals were divided into two groups: stridulating and non-stridulating. After dissection, stridulation was associated with the sex of each individual. Most males (92.2 %, N= 115) emitted sound by stridulation due to the presence of stridulatory organs on the posterior internal surface of their elytra and penultimate tergite, while none of the females (N=92) have such organs. This result is the first report of stridulatory activity in H. odoratus.